High-Efficiency Agrobacterium rhizogenes-Mediated Transgenic Tairy Root Induction of Lens culinaris - Foti, Chrysanthi; Pavli, Ourania I (Agronomy (Basel), 2020)
Previous efforts to transform lentil have been considerably hampered by the crop’s recalcitrant nature, giving rise to particularly low transformation and regeneration frequencies. This study aimed at optimizing an Agrobacterium rhizogenes-mediated transformation protocol for the generation of composite lentil plantlets, comprised of transgenic hairy roots and wild-type shoots. Transformation was performed by inoculating the cut hypocotyl of young lentil seedlings, while optimization involved the use of different bacterial strains, namely R1000, K599 and Arqua, and protocols differing in media composition with respect to the presence of acetosyringone and MES. Composite plantlets had a transgenic hairy root system characterized by an increased number of hairy roots at the hypocotyl proximal region, occasionally showing plagiotropic growth. Overall findings underline that transformation frequencies are subject to the bacterial strain, media composition as well as their combined effect. Among strains tested, R1000 proved to be the most capable of hairy root formation, while the presence of both acetosyringone and MES in inoculation and culture media yielded considerably higher transformation rates. The transgenic nature of hairy roots was demonstrated by the Ri T-DNA-mediated transfer of the rolB2 gene and the simultaneous absence of the virCD sequence of A. rhizogenes. Our findings provide strong evidence that A. rhizogenes-mediated transformation may be employed as a suitable approach for generating composite seedlings in lentil, a species whose recalcitrance severely hampers all efforts addressed to transformation and whole plant regeneration procedures. To the best of our knowledge, this is the first report on the development of a non-laborious and time-efficient protocol for the generation of transgenic hairy roots in lentil, thus providing an amenable platform for root biology and gene expression studies in the context of improving traits related to biotic and abiotic stress tolerance.